PENGARUH FUNDAMENTAL BANK TERHADAP RETURN ON ASET PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 – 2023 - Hutahaean, Thomas F Hutahaean; Benget, Jhon Lismart; Sihombing, Riondi Solomon Zugia (Fakultas Ekonomi Prodi Akuntansi, 2022)
The research results based on a simultaneous test (F test) state that the CAR, BOPO, LDR, NPL variables simultaneously influence the Return On Assets variable. The t test (Partial) shows that the LDR variable has a significant and significant effect on Return On Assets. Data collection technique with a sample size of 108. The value of the coefficient of determination that can be explained by the independent variable used is 0.572 or 57.2% and 42.8% can be explained by other variables. CAR does not have a significant positive influence on the ROA of banking companies listed on the IDX in 2011 - 2016. CAR does not have a positive and significant influence on ROA of banking companies in 2015 - 2023. BOPO has no positive influence on ROA and LDR is significant on ROA of banking companies in 2015 – 2023. LDR has a positive influence on ROA and LDR is significant on ROA of banking companies in 2015 – 2023. NPL does not have a positive influence on ROA and NPL is significant on ROA of banking companies in 2015 – 2023.The coefficient of determination (R2) is 0.572 with 57.2% influencing ROA and 42.8% being determined by other variables, such as NIM and Third Party Funds.